Methods Validation of Pork Authentication in Processed Meat Products (Sausages) Through Densitometry Analysis - Hermanto, Sandra; Rudiana, Tarso; Zein, Muhammad Ihda Hamlu Liwaissunati; Wisudawati, Asih Widi (UIN Sunan Gunung Djati Bandung, 2022)
Analysis of the halalness of food products based on animal origin needs to be carried out, especially for critical food products such as processed meat products (sausages). Some processed meat products are found that they are contaminated by pork in the processing. This research was conducted to determine the validity of the analysis method of pork contamination in one of the processed products (beef, pork, and goat sausages) based on the characteristics of the protein profile. Beef, pork, and goat sausages that have been purchased from supermarkets in Jakarta and South Tangerang are used as the sample.The praparation of sample was preceded by extraction of the sausage protein in PBS buffer pH 7.2. Then, the dissolved protein content was tested, and the protein extract was separated by SDS-PAGE (sodium dodecyl sulphate polyacrylamide gel electrophoresis). The protein profile result from SDS-PAGE separation was followed by densitometric analysis (ImageJ) to obtain biomarker protein candidates. The validation of the analytical method includes the precision (repeatability), test for accuracy, linearity, and robustness of the method by varying the extraction pH. The results show that the protein extract has the differences in protein content and composition for each sample. The SDS-PAGE analysis results show that biomarker protein candidates appeared below 50 kDa which were thought to be the protein fraction of actin. The precision and accuracy test results obtained for each sample have met the required standards, namely with a KV value <5% and a percent recovery value> 95%. The results of the linearity test and the toughness of the method also show that the test method is quite effective in testing the halalness of animal food products, especially in sausage products which are contaminated by pork.